Criteria for studying modality in German: typology and universals - Ferrer Mora, Hang (Revista de Filología Alemana, 2011)
Modality as a linguistic phenomenon is a hotchpotch that includes the study of speakers’ attitudes. However, the first basic issue when dealing with modality is to specify the object of study. In traditional grammars, modal verbs are focused on in detail; then there is sentence modality and in more recent grammars, modal connectors and particles. In the grammars of many natural languages, sentence modality is dealt with in a vague sort of way; in German linguistics, however, it has been widely studied. This paper focuses on sentence modality and particles as expressions of modality. The discussion centres on whether analysis criteria specific to the German language can be extrapolated and applied to typological and universalist linguistics.